Use and records of child health handbook focused on growth and development - Claudia Nery Teixeira Palombo; Luciane Simões Duarte; Elizabeth Fujimori; Áurea Tamami Minagawa Toriyama (SciELO, 2014)
Objective To evaluate the use and records of the Child Health Handbook (CHH), especially growth and development. Method Cross-sectional study with 358 mother-child pairs registered in 12 Primary Health Centers (PHCs) of a small municipality. Mothers were interviewed at the PHC from February to April 2013 using a questionnaire. Data analysis was done using WHO Anthro software, Epi InfoTM and Stata. Results Fifty-three percent of the mothers were carrying the CHH at the time of the interview, similar to the proportion of mothers who were instructed to bring the CHH to health appointments. Annotations in the CHH during the visits were reported by 49%. The vaccination schedule was completed in 97% of the CHH, but only 9% and 8% of the CHH, respectively, contained growth charts and properly completed developmental milestones. Conclusion Low rates of use and unsatisfactory record-keeping in the CHH reinforce the need for investment in professional training and community awareness for the CHH to become an effective instrument of promotion of child health.